THE ROLE OF GREEN INVESTMENT AND ENVIRONMENTAL PERFORMANCE ON FINANCIAL PERFORMANCE WITH MODERATION OF COMPANY SIZE - Rosyid, Rosyid; Mulatsih, Srie Nuning (Univesitas Muhammadiyah Tangerang, 2024)
The study aims to test the impact of green investment and environmental performance on corporate performance with moderation of corporate size. The method of moderate regression analysis with panel data is used in this study. Companies listed in SRI KEHATI, PROPER, and BEI rankings during the 2018-2022 survey period. Research results show that green investment and environmental performance benefit corporate financial performance, but corporate size does not.